The MPK8‐TCP14 pathway promotes seed germination in Arabidopsis. (28th September 2019) - Zhang, Wei; Cochet, Françoise; Ponnaiah, Maharajah; Lebreton, Sandrine; Matheron, Lucrèce; Pionneau, Cédric; Boudsocq, Marie; Resentini, Francesca; Huguet, Stéphanie; Blázquez, Miguel Á.; Bailly, Christophe; Puyaubert, Juliette; et al.
Summary: The accurate control of dormancy release and germination is critical for successful plantlet establishment. Investigations in cereals hypothesized a crucial role for specific MAP kinase (MPK) pathways in promoting dormancy release, although the identity of the MPK involved and the downstream events remain unclear. In this work, we characterized mutants for Arabidopsis thaliana MAP kinase 8 (MPK8). Mpk8 seeds presented a deeper dormancy than wild‐type (WT) at harvest that was less efficiently alleviated by after‐ripening and gibberellic acid treatment. We identified Teosinte Branched1/Cycloidea/Proliferating cell factor 14 (TCP14), a transcription factor regulating germination, as a partner of MPK8. Mpk8 tcp14 double‐mutant seeds presented a deeper dormancy at harvest than WT and mpk8, but similar to that of tcp14 seeds. MPK8 interacted with TCP14 in the nucleus in vivo and phosphorylated TCP14 in vitro . Furthermore, MPK8 enhanced TCP14 transcriptional activity when co‐expressed in tobacco leaves. Nevertheless, the stimulation of TCP14 transcriptional activity by MPK8 could occur independently of TCP14 phosphorylation. The comparison of WT, mpk8 and tcp14 transcriptomes evidenced that whereas no effect was observed in dry seeds, mpk8 and tcp14 mutants presented dramatic transcriptomic alterations after imbibition with a sustained expression of genes related to seed maturation. Moreover, both mutants exhibited repression of genes involved in cell wall remodeling and cell cycle G1/S transition. As a whole, this study unraveled a role for MPK8 in promoting seed germination, and suggested that its interaction with TCP14 was critical for regulating key processes required for germination completion. Significance Statement: We provide evidence that MPK8 participates in the regulation of dormancy and germination via its interaction with the transcription factor TCP14. Although MPK8 phosphorylates TCP14, phosphorylation was not required for the stimulation of TCP14 transcriptional activity by MPK8. Transcriptomic analyses support the involvement of MPK8‐TCP14 pathway in the regulation of dormancy‐to‐germination transition.